Two Decades of Rising Inequality and Declining Poverty in the Lao People's Democratic Republic - Peter Warr; Sitthiroth Rasphone; Jayant Menon (Asian Development Bank (ADB), 2015)
Over the last 2 decades the distribution of private household expenditures has become more unequal in the Lao People's Democratic Republic, with the Gini coefficient rising from 0.311 to 0.364, even though absolute poverty incidence has halved. The increase in inequality was statistically significant and reduced the average rate of poverty reduction per year by about 28%, meaning the actual rate compared with the counterfactual rate that would have occurred if the mean real expenditures had increased at their observed levels but inequality had not changed. When the data are decomposed into rural and urban areas of residence or by province, or by the ethnicity of the household head, the increase in inequality within groups dominates any changes between groups; inequality has increased throughout the country. In contrast, access to publicly provided services has become more equal; disparities in participation rates between richer and poorer groups have diminished.
hdl:11540/5253
Keywords: D31; D39; I39; 330; expenditure inequality; Gini coefficient; Lao PDR; poverty reduction